Thermogenic Characterization and Antifungal Susceptibility of Candida auris by Microcalorimetry - Di Luca, Mariagrazia (J Fungi (Basel), 2019)
Candida auris has emerged globally as a multidrug-resistant fungal pathogen. Isolates of C. auris are reported to be misidentified as Candida haemulonii. The aim of the study was to compare the heat production profiles of C. auris strains and other Candida spp. and evaluate their antifungal susceptibility using isothermal microcalorimetry. The minimum heat inhibitory concentrations (MHIC) and the minimum biofilm fungicidal concentration (MBFC) were defined as the lowest antimicrobial concentration leading to the lack of heat flow production after 24 h for planktonic cells and 48 h for biofilm-embedded cells. C. auris exhibited a peculiar heat production profile. Thermogenic parameters of C. auris suggested a slower growth rate compared to Candida lusitaniae and a different distinct heat profile compared to that of C. haemulonii species complex strains, although they all belong to the Metschnikowiaceae clade. Amphotericin B MHIC and MBFC were 0.5 µg/mL and ≥8 µg/mL, respectively. C. auris strains were non-susceptible to fluconazole at tested concentrations (MHIC > 128 µg/mL, MBFC > 256 µg/mL). The heat curve represents a fingerprint of C. auris, which distinguished it from other species. Treatment based on amphotericin B represents a potential therapeutic option for C. auris infection.